Nanofabrication for Plasmon-Mediated Catalysis via Absorption Engineering - Darmadi, Iwan (My University, 2016)
Localized Surface Plasmon Resonance (LSPR) is a unique property of nano-scale materials. It is a resonant response of the electrons of the material to irradiated light at optical frequencies. One of the interesting effects of the resonance is the significant enhancement of the electromagnetic field surrounding the plasmonic nanoparticle. This enhancement can be utilized for a number of applications, one of them is to enhance the light absorption in small catalyst nanoparticles and thus potentially increase the catalytic reaction rate via photocatalytic (hot electron) mechanisms. It is worth noting that catalysts are indispensable to build an eco-friendly society due to their applications in e.g. waste/pollution treatment and emerging sustainable energy technologies. With this spirit, I developed a nanofabrication concept to enable proof-of-concept experiments of light absorption enhancement in Pt catalyst nanoparticles by the LSPR of an adjacent Ag nanoparticle. Interestingly, the LSPR of the Ag nanoparticles occurs in the visible light spectral range, potentially enabling solar energy harvesting to enhance catalytic reaction using the developed nanostructures. In order to demonstrate the enhancement, I developed three different fabrication methods by modifying the so-called hole-mask colloidal lithography (HCL) nanofabrication platform. Specifically, I investigated three methods for the deployment of the sacrificial layer by testing three different materials, namely, PMMA, chromium, and carbon. The hetero-nanostructures fabricated with the PMMA sacrificial layer exhibited absorption enhancement in the Pt nanoparticles of at least a factor of 8. The expected structure was not successfully attained by the two latter sacrificial layer materials, however. The origins of the failure i.e. the undercut process and the atomic layer deposition are documented and addressed in this report.
Keywords: Nanovetenskap och nanoteknik; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Nanoteknik; Nanoscience & Nanotechnology; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Nano Technology